Does the Weather Contribute to Admissions of Neck of Femur Fractures?. (12th March 2021) - Koizia, Louis J.; Dani, Melanie; Brown, Hannah; Lee, Malcolm; Reilly, Peter; Fertleman, Michael B.
Background: The effects of weather on overall mortality are well documented. Anecdotally, icy conditions are perceived to result in more falls and admissions for neck of femur (NOF) fractures. The aim of this pilot study was to determine whether relationships could be extracted or at least not ruled out by analysing a small dataset, and so give impetus to a larger project. Methods: Seven trauma units across North West London were identified and NOF fracture data extracted for 5 years. Visual inspection of the time series, consideration of the weather on specific days and correlation analysis were used to assess associations between fracture numbers and a variety of weather parameters (temperature, rainfall, wind and ice risk). Results: Overall, 10929 individuals with hip fractures were admitted over the 5-year period. The highest number of admissions in a day was 14. No clear association was found between a weather parameter and daily admissions. However, when accumulated to a weekly timescale, a negative relationship with maximum temperature was found. No seasonal cycle was detected. Conclusion: The lack of a daily relationship and presence of a weekly relationship points to a possible delayed response to weather or insufficient daily data to extract a signal. The inconclusive results also indicate a larger data sample is required in future studies. In addition, even in cold weather an urban environment may not create icy conditions, being ameliorated by the heat island effect and gritting.